История русской жизни с древнейших времен: справочное издание / Иван Забелин - Забелин Иван Егорович (Эксмо, 2008)
Экземпляры: (20200303) / Инвентарный номер: 33829 / Цена: 318.10 / Сис.шифр: 63.3(2) / Авт.знак: З-12 / ГРНТИ: 03 / ББК: 63.3(2)